0024 The occupations at increased risk of copd in the uk biobank cohort. (21st August 2017) - Matteis, Sara De; Jarvis, Deborah; Darnton, Andrew; Fishwick, David; Rushton, Lesley; Cullinan, Paul
Abstract : Background: Occupational hazards are important, preventable causes of COPD but the high-risk occupations are uncertain. In an analysis of current occupation in the UK Biobank cohort we reported 14 jobs of increased risk (De Matteis, S. et al. OEM 2016). Aims and objectives: Our aim was to develop these findings using lifetime job-histories to identify occupations at increased COPD risk, taking into account potential confounders. Methods: We used OSCAR, an online tool that automatically codes full job-histories using the UK Standard Occupational Classification (SOC) v.2000 (De Matteis, S. et al. SJWEH 2016). In 2016 we administered OSCAR to all UK Biobank participants with an email address (n=324, 653). All paid jobs of >6 months duration, were collated and coded. COPD was spirometry-defined as FEV1/FVC< LLN. Prevalence ratios (PRs) for ever-exposure to each job vs. lifetime office work were estimated using Poisson regression adjusted for age, sex, centre and lifetime smoking. Results: Among 116, 375 OSCAR-responders, we analysed the 94 551 with acceptable spirometry data and smoking information. Six occupations showed an increased risk of COPD confirmed by positive exposure-response trends, and in analyses restricted to never-smokers and never-asthmatics. In comparison with our findings for current occupation, some associations were confirmed (e.g. food/drink/tobacco processors: PR 1.70;95% CI:1.17–2.48) while others emerged (e.g. plastics processors: PR 1.86;95% CI:1.09–3.17; agriculture/fishing: PR 1.76;95% CI:1.22–2.55). Conclusions: In order to focus workplace preventive strategies, we are in the process of applying a job-exposure matrix to identify the underlying occupational respiratory hazards.